Kepuasan Pasien Rawat Jalan Terhadap Digitalisasi Pelayanan Kesehatan: Studi di UPT RSUD Arifin Nu’mang Rappang - Muchtar, Adrikah; Astinah Adnan, A.; Hamid, Hariyanti; D, Herman; Ahmad, Jamaluddin; Barisan, Barisan (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2025)
Digitalization in health care is the process of converting analog data or information into digital format which aims to create a connected, efficient, and patient-centered health system, where information flows smoothly, decisions are made based on data and services can be accessed more easily. This study aims to determine the level of satisfaction of outpatients at UPT Arifin Nu'mang Rappang Regional General Hospital. The population of this study was the number of outpatients who sought treatment in November-December 2024 as many as 6,232 people. The research sample was 98 people using incidental sampling technique. The data collection techniques used were observation, questionnaires, and literature studies using quantitative descriptive methods, namely data analysis techniques using descriptive statistical analysis, validity and reliability tests, and simple linear regression analysis using SPSS 21 software. The results of this study indicate that outpatient patient satisfaction has a significant effect on the digitization of health services with a satisfaction level of 73% and 70%, respectively. This is evidenced by the results of the ANOVA test or f test which shows fcount 70.451 with a significance of 0.000 while the t test shows tcount (8.394) > ttable (1.660). The R square value is 42.3%, which means that 42.3% is influenced by patient satisfaction and the remaining 57.7% is influenced by other unknown factors. With this, hospital management needs to formulate strategic steps that can increase the digitalization of health services.